2016
DOI: 10.1002/pip.2775
|View full text |Cite
|
Sign up to set email alerts
|

Process development and comparison of various boron emitter technologies for high-efficiency (~21%) n-type silicon solar cells

Abstract: This paper shows for the first time a comparison of commercial-ready n-type passivated emitter , rear totally diffused solar cells with boron (B) emitters formed by spin-on coating, screen printing, ion implantation, and atmospheric pressure chemical vapor deposition. All the B emitter technologies show nearly same efficiency of~20%. The optimum front grid design (5 busbars and 100 gridlines), calculated by an analytical modeling, raised the baseline cell efficiency up to 20.5% because of reduced series resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…Fraunhofer ISE also used the Ti/Pd/Ag evaporation method employing photolithography for the front contact . Second, it is difficult to control the boron doping profile for low recombination current density, and a number of research studies have shown that this is a barrier for the industrialization of n‐type silicon solar cells . In addition, although IBC solar cells have reached a record efficiency of over 26%, the process flow is complicated and uses ion implantation and the photolithography method to realize the pattern at the rear side, which is challenging for commercialization .…”
Section: Introductionmentioning
confidence: 99%
“…Fraunhofer ISE also used the Ti/Pd/Ag evaporation method employing photolithography for the front contact . Second, it is difficult to control the boron doping profile for low recombination current density, and a number of research studies have shown that this is a barrier for the industrialization of n‐type silicon solar cells . In addition, although IBC solar cells have reached a record efficiency of over 26%, the process flow is complicated and uses ion implantation and the photolithography method to realize the pattern at the rear side, which is challenging for commercialization .…”
Section: Introductionmentioning
confidence: 99%
“…High photovoltaic (PV) conversion efficiencies can be reached by this way with recently 20.8% obtained on a pilot line of screen‐printed n‐type PERT (n‐PERT) solar cells . However, a keen interest toward single‐side doping techniques has been seen these past few years . Compared with the double‐side doping of the BBr 3 and BCl 3 diffusions, they can strongly simplify the solar cells process flows and thus reduce the production cost of solar cells with boron‐doped layers.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the double‐side doping of the BBr 3 and BCl 3 diffusions, they can strongly simplify the solar cells process flows and thus reduce the production cost of solar cells with boron‐doped layers. Most of them have demonstrated high boron emitter electrical qualities such as spin‐on coating, screen printing, codiffusion from atmospheric pressure chemical vapor deposition (APCVD) of doped layers, and ion implantation . Some of these single‐side doping techniques are already used in high‐efficiency n‐type solar cells …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…이처럼 우수한 웨이퍼 품질과 inactive doping의 차이에 의한 boron diffusion layer의 낮은 saturation current density (J 0e )는 N-type 태양전지의 장점이다 [4]. 하지만 이러한 장점에도 불구하고 boron diffusion layer의 형성, passivation에 연관된 기술적 도전과 비용 때문에 P-type 실리콘 태양전지가 주류를 이루고 있으며 다양 한 boron diffusion 기술들이 현재까지 조사 및 사용 되고 있지만 뚜렷하게 우위에 있는 기술은 나오고 있 지 않은 상황이다 [5]. …”
unclassified